Sprawiedliwe nierówności a aksjologia ładu instytucjonalnego - Woźniak, Michał Gabriel (Annales. Etyka w Życiu Gospodarczym, 2008)
The author of article proves that in the era of the globalization the institutional order of national economy is influenced by the distorted competition which results in domination of the managers and technicians of great corporations. It is their businesses that define the economic policy. In the world of asymmetric information, oligopolistic competition, political market and progressive commercialization of the axiological sphere the rules of thinking and acting are merely reduced to the strategy of self-advantage. This situation results in ineffective institutional protection at the global, regional and national levels. To remove social inequalities effectively it is necessary to have control over the dominating groups in society and to develop coherent norms of institutional protection. There is also a need for the development of human capital and its modernization as a common notion of moral values of society and the individual.